Personality characteristics of Serbian male wheelchair and professional basketball players [Charakteristika osobnosti srbských basketbalistů-vozíčkářů a profesionálních basketbalistů] - Fadilj Eminović; Ljubica Bačanac; Saša Jakovljević; Ljubiša Lazarević; Kasum Goran (Palacky University, 2012)
BACKGROUND: Sport, as social phenomena, may achieve a very positive influence on health and the social state of people with disability who practice it. In sport activities of athletes with disability, team sports may take a very important place. OBJECTIVE: The aims of this study were: a) to investigate personality characteristics of male professional basketball players and wheelchair basketball players, b) to compare these characteristics of two kinds of athletes. METHODS: For the purposes of this study, professional basketball players (N = 29) and wheelchair basketball players (N = 25) had completed a Cattell 16PF questionnaire which estimated personality characteristics. Differences between two groups of participants were calculated by t-test for small samples. RESULTS: Results demonstrated the existence of differences in the expression of certain forms of behaviour within certain dimensions of personality between these two groups. Wheelchair basketball players had higher scores at factor M - Abstractedness (t = -1.889; p = 0.046), which means that they are more preoccupied by themselves and their inner mental life. Wheelchair basketball players had lower scores, on factors: C - Emotional Stability (t = 2.097; p = 0.041), E - Dominance (t = 3.530; p = 0.001), F - Liveliness (t = 2.658; p = 0.010) and N - Privateness (t = 2.527; p = 0.015). CONCLUSIONS: Wheelchair basketball players are, compared with professional basketball players, more emotive; they have a lack of self-esteem, less ready for teamwork and collaboration; they are naive and unpretentious. Considering these results, coaches who are involved in work with wheelchair basketball players have to adjust their methods of trainings, especially those coaches who were working with basketball players without disability. Also, coaches' influence can stimulate eventual changes in some above mentioned characteristics of wheelchair basketball players in more desirable course. [VÝCHODISKA: Sport jak sociální fenomén může mít velmi pozitivní vliv na zdraví a sociální situaci osob s postižením, které jej provozují. Velmi důležité místo mezi aktivitami postižených sportovců mohou zaujímat kolektivní sporty. CÍLE: Studie měla tyto cíle – a) prošetřit charakteristiku osobnosti profesionálních basketbalistů a basketbalistů-vozíčkářů; b) porovnat tyto charakteristiky dvou druhů sportovců. METODIKA: Pro účely této studie profesionální basketbalisté (N = 29) a basketbalisté-vozíčkáři (N = 25) vyplnili dotazník Cattell 16PF, v němž jsou ohodnoceny charakteristiky osobnosti. Rozdíly mezi oběma skupinami účastníků byly spočteny pomocí t-testu pro malé vzorky. VÝSLEDKY: Výsledky prokázaly výskyt rozdílů mezi oběma skupinami ve vyjádření určitých forem chování v rámci určitých dimenzí osobnosti. Basketbalisté-vozíčkáři zaznamenali vyšší skóre u faktoru M – roztržitost (t = –1,889; p = 0,046), což znamená, že se více za bývají sami sebou a svým vnitřním duševním stavem. Basketbalisté-vozíčkáři zaznamenali nižší skóre u faktorů C – emocionální stabilita (t = 2,097; p = 0,041), E – dominance (t = 3,530; p = 0,001), F – živost (t = 2,658; p = 0,010) a N – odloučenost (t = 2,527; p = 0,015). ZÁVĚRY: Basketbalisté-vozíčkáři jsou ve srovnání s profesionálními basketbalisty více emocionální; mají nižší sebeúctu, jsou méně připravení na týmovou práci a spolupráci; jsou naivní a skromní. Na základě těchto výsledků musejí trenéři, kteří pracují s basketbalisty-vozíčkáři, přizpůsobit své tréninkové metody, zejména ti trenéři, kteří dříve pracovali s hráči bez postižení. Vliv trenérů může také podnítit eventuální změny v některých z výše uvedených charakteristik basketbalistů-vozíčkářů žádoucím směrem.]